Beyond the texts: an archaeological portrait of ancient Israel and Judah - Dever, William G. (SBL Press, 2017)
"William G. Dever offers a welcome perspective on ancient Israel and Judah that prioritizes the archaeological remains to render history as it was--not as the biblical writers argue it should have been. Drawing from the most recent archaeological data as interpreted from a nontheological point of view and supplementing that data with biblical material only when it converges with the archaeological record, Dever analyzes all the evidence at hand to provide a new history of ancient Israel and Judah that is accessible to all interested readers"--